2011
DOI: 10.1007/s00534-011-0490-6
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of ultrasound‐guided percutaneous argon‐helium cryoablation of hepatocellular carcinoma

Abstract: PurposeTo evaluate the efficacy and safety of ultrasound (US)-guided percutaneous argon-helium cryoablation for hepatocellular carcinoma (HCC) and determine appropriate indications.MethodsWe reviewed outcomes of 300 HCC patients who underwent US-guided percutaneous cryoablation.ResultsOverall, 223 tumors (mean diameter 7.2 ± 2.8 cm) in 165 patients were incompletely ablated, while 185 tumors (mean diameter 5.6 ± 0.8 cm, P = 0.0001 vs. incomplete ablation) in 135 patients were completely ablated. Nineteen patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 22 publications
2
48
0
Order By: Relevance
“…We therefore sought to find more effective treatment strategies. Since argon-helium cryosurgery system (AHCS) could effectively kill tumor cells [10], in this study, we further explored the anti-tumor effect by combining AHCS with TACE.…”
Section: Introductionmentioning
confidence: 99%
“…We therefore sought to find more effective treatment strategies. Since argon-helium cryosurgery system (AHCS) could effectively kill tumor cells [10], in this study, we further explored the anti-tumor effect by combining AHCS with TACE.…”
Section: Introductionmentioning
confidence: 99%
“…Although some early review articles reported insufficient data to support or refute cryotherapy for HCC [90], many recent studies have shown that image-guided percutaneous cryoablation is safe and effective for treating HCC [82,83,84,91,92]. A single meta-analysis performed by Huang et al [93] investigated the role of cryoablation in comparison to RFA in treating unresectable HCC and showed an advantage for RFA over cryotherapy in terms of complication rates (OR 2.80; 95% CI, 1.54-5.09) and local tumor recurrence (OR 1.96; 95% CI, 1.12-3.42).…”
Section: Local Ablative Therapymentioning
confidence: 99%
“…Cryoshock is a significant systemic adverse effect of cryoablation, which has been reported to occur in 1-2 % of all hepatic cryoablation [41,42]. We did not experience any case of cryoshock.…”
Section: Discussionmentioning
confidence: 76%